Easy and cost-efficient method for tumour localization in patients with breast cancer undergoing neoadjuvant chemotherapy followed by breast conservation therapy. Issue 9 (22nd June 2021) - Biswas, D.; Chigurupati, S. V.; Pandey, M.
Abstract : This article describes placement of a radio-opaque clip for tumour localization to facilitate resection in patients undergoing neoadjuvant chemotherapy followed by breast conservation therapy. Use of a radio-opaque marker made of stainless steel K-wire and use of a Trucut ® needle with a blunt stylet for wire placement in the breast tumour bed is a safe, indigenous, and cost-effective method for tumour localization.